Digital Technologies on Mathematics Education at the Covid-19 Lockdown Situation in India - Kaushik Das (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2021)
This paper introduces digital technologies and mathematics education at the Covid-19 Lockdown situation in India. The researcher focused on ICT-based tools or techniques for supporting innovative teaching and learning processes in mathematics and the study of these processes including the support that has to be given to teachers and educators. Researchers involved in mathematics education with digital technologies are especially touchy to the problems raised by the current fragmentation of the field. ICT-based technologies are likewise going to be the extraordinary friend in need of the socio-economic in rural India. The data were analyzed using both descriptive and as well as inferential statistics and the methodology of the study is a mixed type involving interpretative, analytical study of documents,  survey questionnaire and study both primary & secondary sources, like books, university news, expert opinion, articles, journals, thesis, and websites, etc. Finally, meaningful suggestions are offered.